Impact of Climate Change and Community Adaptation of Bajo Tribe - Reka Rahmawati; Kahirun Kahirun; La Ode Midi (Newinera Publisher, 2020)
The purpose of this study is to determine the effects of climate change and the adaptation forms of the Bajo tribe that are felt in the coastal regions of Wawonii Indonesia. This research method is the type of data used in this study is the type of qualitative data and surveys, data collection techniques used in this study were interviews, discussion, questionnaire distribution, and field observations. The results showed that the impact of climate change in the Langara Laut village can be felt by increasing the cost of residential renewal activities by a percentage of 52.5% of respondents with 21 people, then shifting livelihoods to a percentage of 22.5% with respondents 9 lives, and the risk of activities at sea in the Bajo tribe community increased as a percentage 25.0% with respondents 10 people. As for the form of adaptation carried out by the Bajo Tribe community in Langara Laut by making stronger residential measures (Protective) a percentage of 52.5% with respondents 21 people, then diversifying livelihoods/diversification is part of a form of relocation action percentage of 22.5% with respondents 9 people, and the use of transportation (ships) and fishing gear that is more effective in other words a form of accommodation measures 25.0% with respondents 10 people.